MEMBANGUN SPRITUALITAS DI TENGAH MENGUATNYA KDRT TERHADAP PEREMPUAN KAJIAN PAK DAN SPRITUALITAS - Lainatta, Meilany (Institut Agama Kristen Negeri (IAKN) Ambon, 2023)
Abstract: This research aims to determine the ideas and practical matters of Christian Religious Education in building spirituality for women amidst increasing acts of domestic violence. The article below will look at how women who are victims of domestic violence can build spirituality in conditions when they experience violence which causes women to live in suffering and misery. This research involved a woman, who was in the Southwest Maluku Regency area. The research method used is a qualitative method based on case studies, interviews, analyzing and then providing argumentative and critical responses related to the research so that ideas and practical matters can be obtained through Christian Religious Education in building spirituality for women who are victims of violence. Despite the visible conditions, women victims of domestic violence are able to think critically and be firm in making decisions to avoid all forms of violence. This is what then builds women's spirituality in facing this reality.Keyword: KDRT,Spirituality, PAK